Perancangan Penjadwalan Pinjaman Fixed Asset Desa dengan Penerapan Algoritma Greedy - Asep Ririh Riswaya; Jajat Sudrajat; Dheni Apriantsani Budiman (INTERNAL (Information System Journal), 2023)
To facilitate and streamline the activities of recording or inputting asset data in CIPELAH VILLAGE, computerization is needed in this village to schedule fixed asset loans. The fixed asset loan scheduling system is a system designed to help ease the asset cation staff when managing assets which are still manual or in writing. The research method used is literature study, field study, interview, observation, and the system development technique used is OOAD (Object Oriented Analysis Design) and the method used is the GREEDY method. The implementation and system testing stage is a stage that is carried out after the system has been analyzed and designed in detail, this stage is also the stage of implementing the system for operation. The programming language used is HTML, PHP with PHPMyAdmin database.